Pengaruh Penggunaan Media Gambar Berseri Terhadap Keterampilan Menulis Karangan Narasi Pada Siswa Kelas IV SD Negeri Ngompro 1 - Dwi Indah Utami; Uci Ulfa Nur Afifah; Novia Rahma Rista Utami (CV Edujavare Publishing, 2025)
This study aims to develop 3D animated story media using the Directed Reading Thinking Activity (DRTA) strategy to improve the reading comprehension skills of fourth-grade elementary school students. The research employed the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The subjects were students from an elementary school in Kudus Regency, Central Java, Indonesia. The development produced a 3D animated media product along with a user guidebook. Validation results from media experts, material experts, and elementary learning device experts indicated that the developed media met the feasibility criteria in terms of visual quality, content appropriateness, and instructional usability. Therefore, the 3D animated story media based on the DRTA strategy is considered effective in supporting the improvement of students’ reading comprehension skills.